2015
DOI: 10.1007/s00431-015-2500-1
|View full text |Cite
|
Sign up to set email alerts
|

Optimal noninvasive assessment of initial left ventricular dysfunction in children with ectopic atrial tachycardia

Abstract: TIC occurred in 18.6% of children with EAT. Initial LV dysfunction assessed by the TDI-MPI and E/E' is associated with elevated plasma NT-proBNP, even the LVEF is normal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…We suggest that a com-parison of the measured Sm data in children with EAT to available pediatric Sm normal values would have improved the statistical power of their analysis and therefore emphasizing the high value of a TDI investigation of the LV in children with EAT. We further want to strengthen the value of the recent data from Ge et al [1] in contrast to the overaged findings from Swaminathan et al [3]. We want to thank the authors for addressing the usefulness of TDI measurements as alternatives to the conventionally used LVEF.…”
Section: To the Editormentioning
confidence: 86%
See 3 more Smart Citations
“…We suggest that a com-parison of the measured Sm data in children with EAT to available pediatric Sm normal values would have improved the statistical power of their analysis and therefore emphasizing the high value of a TDI investigation of the LV in children with EAT. We further want to strengthen the value of the recent data from Ge et al [1] in contrast to the overaged findings from Swaminathan et al [3]. We want to thank the authors for addressing the usefulness of TDI measurements as alternatives to the conventionally used LVEF.…”
Section: To the Editormentioning
confidence: 86%
“…We may add that even without a large experience, high-quality acquisition and analysis of the Sm can be easily performed. We hope that with more interesting studies like this from Ge et al [1], this simple quantification of systolic LV function will become an easy available routine tool for all sonographers and physicians.…”
Section: To the Editormentioning
confidence: 94%
See 2 more Smart Citations
“…1 Before and 3 months after the HSCT, the presence of a possible functional myocardial impairment was investigated with the use of the tissue Doppler imaging (TDI) parameters, peak mitral annular systolic velocity (Sm), and tricuspid annular peak systolic velocity (S 0 ). In a pediatric cohort suffering from atrial tachycardia, Ge et al 2 found that left ventricular (LV) function assessed with the TDI parameter Sm advances an early detection of LV dysfunction. In agreement to ElMarsafawy et al, 1 Klitsie et al 3 found that TDI parameters were able to detect subclinical impairment of systolic biventricular function in children with congenital heart defects.…”
mentioning
confidence: 99%